Optimal shooting cadence in the laser-run trial of modern pentathlon - Maddalena, T.; Bacot, V.; Cohen, C.; Clanet, C. (Proceedings, 2020)
In the laser-run trial in modern pentathlon, athletes must perform series of five successful shots with a laser pistol. A miss does not lead to a penalty but costs the time needed to lower the arm, charge the weapon and raise the arm. Pentathletes face the following dilemma: is it better to shoot fast or accurately? We investigate experimentally the effect of the shooting cadence on the accuracy. We then predict the consequence of this unavoidable speed-accuracy tradeoff in terms of total time needed to succeed the specific trial of laser-run. We find an optimal shooting cadence for each athlete, which minimizes this time.